2007
DOI: 10.1128/mcb.01339-06
|View full text |Cite
|
Sign up to set email alerts
|

Rbm15 Modulates Notch-Induced Transcriptional Activation and Affects Myeloid Differentiation

Abstract: RBM15 is the fusion partner with MKL in the t(1;22) translocation of acute megakaryoblastic leukemia. To understand the role of the RBM15-MKL1 fusion protein in leukemia, we must understand the normal functions of RBM15 and MKL. Here, we show a role for Rbm15 in myelopoiesis. Rbm15 is expressed at highest levels in hematopoietic stem cells and at more moderate levels during myelopoiesis of murine cell lines and primary murine cells. Decreasing Rbm15 levels with RNA interference enhances differentiation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 53 publications
(53 reference statements)
3
73
0
1
Order By: Relevance
“…4C). Consistent with a very recent study, in which ectopically expressed OTT localizes in the nucleus (26), endogenous OTT localized in the nucleus (Fig. 4A).…”
Section: Yy Is Not Essential For Ott-bsac-dependent Transcriptional Asupporting
confidence: 77%
See 2 more Smart Citations
“…4C). Consistent with a very recent study, in which ectopically expressed OTT localizes in the nucleus (26), endogenous OTT localized in the nucleus (Fig. 4A).…”
Section: Yy Is Not Essential For Ott-bsac-dependent Transcriptional Asupporting
confidence: 77%
“…In addition, knockdown of OTT/RBM15 gene using RNA interference promotes myeloid differentiation (26), suggesting an inhibitory role for OTT in myeloid and megakaryocyte development. These results are consistent with our present study, in which OTT might act as a transcriptional repressor via interaction with HDAC3 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[85]. Interestingly, there is a SHARP-like protein in mouse and men, Rbm15/OTT1, that is implicated in acute megakaryoblastic leukemia [86,87] and has been shown to interact with RBP-J, although the RBP-J binding site of SHARP is not conserved in Rbm15/ OTT1 [88]. Rbm15/OTT1 deficient mice are characterized by a loss of peripheral B-cells and an increase in stem-myeloid-and megakaryocyte progenitors [89].…”
Section: Epigenetic Regulation Of Notch Target Genesmentioning
confidence: 99%
“…It has been shown that zebrafish Jagged2 expression in presumptive MCCs induced activation of zebrafish Notch3 in neighboring cells, blocking MCC fate and driving the alternative transporting epithelial cell fate. In addition, a Hes1-related protein was involved (Ma et al, 2007). In Xenopus, ciliated cells express Delta ligands to activate Notch signaling (and Hes-related proteins), inhibiting the selection of ciliated cells by neighboring epidermal cells (Deblandre et al, 1999).…”
Section: The Primary Function Of Notch Signaling In Lung Epithelial Cmentioning
confidence: 99%